An anti-oxidation coating for nickel-iron based alloy surface

The lanthanum zirconate antioxidant coating was prepared on the surface of the nickel-iron-based alloy by pulsed laser deposition, which solved the problem of low oxidation resistance of the existing coating in saturated water vapor environment, achieved effective protection in high-temperature steam environment, and extended the service life of the alloy.

CN116254508BActive Publication Date: 2025-03-14HUANENG POWER INT INC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310018107.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-03-14
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The existing antioxidant coating has low oxidation resistance in saturated water vapor environments and cannot effectively protect the surface of nickel-iron-based high-temperature alloys, resulting in the boiler tube being easily corroded in high-temperature steam environments.

Method used

A lanthanum zirconate antioxidant coating was deposited on the surface of the nickel-iron-based alloy by pulsed laser deposition. By controlling the parameters such as substrate temperature, laser energy, pulse frequency and protective atmosphere, a coating with excellent antioxidant properties was prepared.

Benefits of technology

The antioxidant performance of the lanthanum zirconate coating is significantly improved under saturated water vapor environment, effectively preventing oxidative corrosion on the surface of nickel-iron-based high-temperature alloys, extending the service life of the alloy, and not affecting the mechanical properties of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116254508B_ABST
    Figure CN116254508B_ABST
Patent Text Reader

Abstract

The invention provides an anti-oxidation coating for the surface of nickel-iron-based alloy, which is prepared by the following method, with nickel-iron-based alloy as substrate, and a lanthanum zirconate anti-oxidation coating is deposited on the substrate surface using a pulsed laser deposition method; during the pulsed laser deposition process, the substrate temperature is 550-800°C, the laser energy is 200-400J, the pulse frequency is 2-6Hz, the spacing between the lanthanum zirconate target and the substrate is 4-5cm, and a mixed atmosphere of oxygen and an inert gas with a volume ratio of 4-6:1 is used as a protective atmosphere. The obtained lanthanum zirconate anti-oxidation coating not only has good interface bonding with the nickel-iron-based high-temperature alloy, but also has good anti-oxidation performance under a saturated water vapor environment, and can achieve the purpose of alloy protection without affecting the mechanical properties of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-oxidation film materials, and in particular to an anti-oxidation coating for the surface of a nickel-iron based alloy. Background Art

[0002] In order to improve the thermal efficiency of power plants, reduce coal consumption and reduce pollution, it is necessary to continuously improve coal-fired power generation technology. Countries around the world are committed to developing coal-fired units with higher temperature and higher pressure parameters. High-temperature alloy materials can withstand high temperatures and pressures. The research and development of high-temperature alloys and related technologies has important political, economic and social significance for my country's development of low-energy consumption and high-efficiency power generation technology. Nickel-iron-based high-temperature alloys have good cold and hot processing properties, long-term organizational stability, and low-cost advantages through precipitation strengthening. They are expected to be widely used in advanced ultra-supercritical coal-fired units. However, during boiler operation, the alloy is extremely susceptible to external flue gas corrosion caused by coal powder combustion and steam oxidation corrosion caused by high-temperature steam inside the boiler tube, which causes the heating surface boiler tube to become thinner or the material to weaken, posing a great threat to the safe operation of the unit.

[0003] Preparing a coating on the surface of a nickel-iron-based high-temperature alloy to further protect the alloy matrix is ​​an effective method to improve the service life and reliability of the material. At present, there are some reports based on anti-oxidation coatings, but their performance is not ideal, and their anti-oxidation performance is low in a saturated water vapor environment. Therefore, it is of great significance to further optimize the anti-oxidation coating and improve its anti-oxidation performance in a saturated water vapor environment to meet the requirements of high-temperature boilers in coal-fired power generation technology. Summary of the invention

[0004] Therefore, the object of the present invention is to provide an anti-oxidation coating for the surface of nickel-iron based alloy, so as to solve the technical problem that the existing anti-oxidation coating has low anti-oxidation performance in a saturated water vapor environment.

[0005] The present invention provides a method for preparing an anti-oxidation coating on the surface of a nickel-iron-based alloy, comprising the following steps:

[0006] Preparation of lanthanum zirconate target;

[0007] A lanthanum zirconate anti-oxidation coating is deposited on the surface of a nickel-iron-based alloy by a pulsed laser deposition method; during the pulsed laser deposition process, the substrate temperature is 550-800°C, the laser energy is 200-400J, the pulse frequency is 2-6Hz, the distance between the lanthanum zirconate target and the substrate is 4-5cm, and a mixed atmosphere of oxygen and inert gas with a volume ratio of 4-6:1 is used as the protective atmosphere.

[0008] The nickel-iron based alloy of the present invention is a conventional alloy, and its components are Cr: 15-20%, C: 0.02-0.1%, B: 0-0.01%, Ti: 0.5-2.0%, Al: 1.0-3.5%, Si: ≤0.8%, Co: 0-3.0%, W: 0-3.0%, N: 0-0.01%, Fe: 15-40%, and the balance is Ni.

[0009] Furthermore, the deposition time of pulsed laser deposition is 3-4h.

[0010] Furthermore, the laser energy of the pulsed laser deposition is 200-300J.

[0011] In the present invention, the inert gas is a conventional inert gas such as argon and helium.

[0012] Furthermore, the thickness of the lanthanum zirconate anti-oxidation coating is 1-3 microns.

[0013] Furthermore, the preparation method of the lanthanum zirconate target comprises the following steps: using lanthanum salt and zirconium salt as starting materials, dispersing the starting materials in anhydrous ethanol and performing a ball milling in the presence of a grinding medium; drying and compacting the ball milled product into an embryo body, and sintering the embryo body once; ball milling and pressing the embryo body after the first sintering; and sintering the pressed embryo body for a second time to obtain a lanthanum zirconate target.

[0014] Furthermore, the lanthanum salt is lanthanum nitrate, and the zirconium salt is zirconium oxychloride. Preferably, the molar ratio of lanthanum nitrate to zirconium oxychloride is 1:1.

[0015] Furthermore, the mass ratio of the starting material to anhydrous ethanol and grinding medium is 1:2-4:4-8. Preferably, the grinding medium is zirconia balls.

[0016] Further, the primary ball milling and / or secondary ball milling is ball milling on a planetary ball mill for 16-24 hours; and / or, the drying method is drying at a temperature of 80°C-100°C for 48h-72h; and / or, the primary sintering is: heating to 1000-1100°C at a heating rate of 3-5°C / min and keeping it at this temperature for 2-3h, and then cooling it at a cooling rate of 10-15°C / min; and / or, the pressing pressure is 200-300MPa, and the time is 5-10min; and / or, the secondary sintering is heating to 1300-1500°C at a heating rate of 3-5°C / min and keeping it at this temperature for 2-3h, and then cooling it at a cooling rate of 10-15°C / min.

[0017] The present invention also provides an anti-oxidation coating for the surface of a nickel-iron-based alloy prepared by any of the above-mentioned preparation methods; preferably, the chemical composition of the anti-oxidation coating is lanthanum zirconate La2Zr2O7.

[0018] The present invention also provides a method for preparing a nickel-iron-based alloy with an anti-oxidation coating on the surface, including any of the above-mentioned methods for preparing the anti-oxidation coating on the surface of the nickel-iron-based alloy.

[0019] The present invention also provides a nickel-iron based alloy with an anti-oxidation coating on the surface obtained by the above-mentioned preparation method.

[0020] The technical solution of the present invention has the following advantages:

[0021] 1. The present invention provides a method for preparing an anti-oxidation coating on the surface of a nickel-iron-based alloy. The lanthanum zirconate anti-oxidation coating is prepared by a pulsed laser deposition method, and the substrate temperature is controlled to be 550-800°C, the laser energy is 200-400J, the pulse frequency is 2-6Hz, the distance between the lanthanum zirconate target and the substrate is 4-5cm, and a mixed atmosphere of oxygen and inert gas with a volume ratio of 4-6:1 is used as a protective atmosphere, and the equilibrium pressure is 10-15Pa.

[0022] The difficulty of preparing coatings on nickel-iron-based alloys by pulsed laser deposition is far greater than the difficulty of preparing coatings on other substrates such as single crystal substrates. This is because the surface quality of nickel-iron-based alloys is poor and they are easily oxidized in high-temperature environments. Improper adjustment of single factors such as high temperature, too large oxygen volume fraction in the working chamber atmosphere, and excessive laser energy, or improper coordination of multiple parameters will lead to oxidation of the nickel-iron-based alloy itself and a decrease in tensile mechanical properties. For a specific lanthanum zirconate target and a specific nickel-iron-based alloy substrate, the present invention requires overall coordination of multiple parameters in the pulsed laser deposition process, that is, the heating temperature of the substrate is 550-800°C, the protective atmosphere is a mixed atmosphere of oxygen and inert gas with a volume ratio of 4-6:1, the equilibrium pressure is 10-15Pa, the laser energy is 200-400J, the pulse frequency is 2-6Hz, and the distance between the target and the sample is 4-5cm. Under the optimal combination of various pulse working parameters in the present invention, an excellent anti-oxidation coating for the surface of nickel-iron-based alloy can be obtained. The obtained lanthanum zirconate anti-oxidation coating not only has good interface bonding with the nickel-iron-based high-temperature alloy, but also has good anti-oxidation properties in a saturated water vapor environment, and can achieve the purpose of alloy protection without affecting the mechanical properties of the alloy.

[0023] When preparing the coating on the nickel-iron-based alloy, the present invention uses a mixed atmosphere of high-purity argon and high-purity oxygen with a volume ratio of 4-6:1 as the working gas. On the one hand, the all-oxygen working environment easily leads to oxidation of the alloy. On the other hand, Ar gas is easily ionized, and the plasma plume can collide with Ar atoms in the cavity to ionize secondary electrons and Ar atoms. + Ion, Ar + Under the action of the power plant, the ions obtain high kinetic energy to bombard the target material, causing more atoms or molecules on the target surface to sputter and escape, thereby accelerating the coating deposition rate. Therefore, Ar as an ambient gas does not participate in the reaction, and mainly affects the internal energy and kinetic energy of the plasma formed after the laser interacts with the target material, as well as the diffusion coefficient and mean free path on the substrate. Oxygen as a reaction gas effectively compensates for oxygen defects in the coating, which has an important influence on the coating composition and structure.

[0024] In addition, too high a temperature can easily cause oxidation of the alloy, but the lower the temperature, the better the effect. When the plasma reaches the substrate, it will be adsorbed by the substrate surface. When the substrate temperature is too low, the diffusion of the adsorbed atoms is not easy to proceed, and it is easy to form a low-density film with a rough surface. When the substrate temperature rises, the thermal vibration frequency of the base atoms related to the temperature also increases, and the activity of the surface adsorbed atoms is greatly enhanced. In some preferred embodiments, the temperature is controlled to be 550-800°C. This temperature is moderate, which can not only ensure that the alloy substrate will not oxidize, but also balance the adsorption and diffusion of atoms. The coating thickness can gradually increase over time and the surface morphology and composition are uniform.

[0025] For different target materials, the diffusion free path of the plasma beam is different, and the requirements for pulse laser parameters are very different. In some preferred embodiments, by controlling the laser energy to 200-300J, the oxidation resistance of the nickel-iron-based high-temperature alloy is improved.

[0026] 2. The method for preparing an antioxidant coating on the surface of a nickel-iron-based alloy provided by the present invention comprises the following steps: using lanthanum salt and zirconium salt as starting raw materials, dispersing the starting raw materials in anhydrous ethanol and performing a ball milling; drying and compacting the ball milled product into an embryo body, and performing a sintering of the embryo body; performing a second ball milling and pressing of the embryo body after the first sintering; performing a second sintering of the pressed embryo body to obtain a lanthanum zirconate target; and using a pulsed laser deposition method to deposit a lanthanum zirconate layer on the surface of a nickel-iron-based alloy sample to obtain a lanthanum zirconate antioxidant coating.

[0027] Since lanthanum zirconate is a stable compound, the difficulty in densifying the lanthanum zirconate target is a key problem that needs to be solved in the preparation process of the target. The density is mainly related to the two factors that make up its raw materials, namely lanthanum salts, lanthanum salts are difficult to sinter, and the lanthanum zirconate compound shrinks slowly during the sintering process. Using the powder pressing method adopted by the existing traditional technology, on the one hand, the powder pressing performance is poor, and the obtained blank has a low density. On the other hand, the shrinkage rate during the sintering process of the pressed green is large, which is easy to cause cracking and warping. In addition, long-term sintering is required, and if the insulation time is too long during the sintering process, it is easy to cause the problem of element loss, which in turn leads to changes in the microscopic composition of the target material or even more serious phase changes.

[0028] In the present invention, the raw materials lanthanum salt and zirconium salt are dispersed in anhydrous ethanol solvent, and the particle interface introduces a liquid phase. The introduction of the liquid phase is conducive to the dissolution of the sharp protrusions of the solid particles, so that the free energy of the particle surface is reduced. After sintering, mass transfer can eliminate the surface gaps of the particles. Furthermore, ball milling can effectively reduce the particle size of the powder, increase the lattice distortion of the powder, reduce the sintering energy barrier, and improve the sintering activity. The whole process makes it possible to obtain a dense target material in a short time, avoiding the problem of target material composition changes caused by a long sintering time. From the micro-element EDS spectrum analysis of the embodiment, it can also be seen that the coating obtained by using the target material has high component retention. From the relationship diagram of the final treatment temperature of the target material and the relative density of the target material, it can be seen that a high-density target material can be obtained by sintering in a short time. In particular, the secondary sintering is controlled to heat up to 1300-1500°C at a heating rate of 3-5°C / min and keep at this temperature for 2-3h, and then cool down at a cooling rate of 10-15°C / min, so that the oxidation resistance of the nickel-iron based high temperature alloy is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is a graph showing the relationship between the final processing temperature of the target material and the density of the target material in Experimental Example 1.

[0031] Figure 2 This is the working window for preparing a lanthanum zirconate coating on a nickel-iron-based high-temperature alloy using a pulsed laser deposition method in Example 1 of the present invention.

[0032] Figure 3 This is the X-ray diffraction pattern of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 1 of the present invention.

[0033] Figure 4 This is the SEM morphology of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 1 of the present invention.

[0034] Figure 5 This is the EDS spectrum of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 1 of the present invention.

[0035] Figure 6 This is the working window for preparing a lanthanum zirconate coating on a nickel-iron-based high-temperature alloy using a pulsed laser deposition method in Example 2 of the present invention.

[0036] Figure 7 This is the SEM morphology of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 2 of the present invention.

[0037] Figure 8 This is the EDS spectrum of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 2 of the present invention.

[0038] Fig. 9 This is the SEM morphology of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 3 of the present invention.

[0039] Fig.10 This is the SEM morphology of the nickel-iron based alloy with an anti-oxidation coating on the surface in Comparative Example 1 of the present invention.

[0040] Fig.11 It is the X-ray diffraction pattern of the nickel-iron based alloy with an anti-oxidation coating on the surface in Comparative Example 2 of the present invention.

[0041] Fig.12 These are the weight gain data of the nickel-iron-based high-temperature alloys with lanthanum zirconate coatings prepared in Examples 1-3 and Comparative Examples 1-2 in a saturated steam environment at 650°C for 1000 hours. DETAILED DESCRIPTION

[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0043] If the specific experimental steps or conditions are not specified in the embodiments, the operation or conditions of the conventional experimental steps described in the literature in this field can be carried out. If the manufacturer is not specified in the reagents or instruments used, they are all conventional reagent products that can be obtained commercially. In the following embodiments and comparative examples, the nickel-iron based sample, the nickel-iron based alloy (sample) or the nickel-iron based high temperature alloy (sample) are all the same substance, and its composition is Cr: 18%, C: 0.1%, Ti: 1.5%, Al: 1.5%, Co: 0.1%, W: 1.0%, N: 0.01%, Fe: 30%, and the balance is Ni.

[0044] Example 1

[0045] The present embodiment provides an anti-oxidation coating for the surface of a nickel-iron-based alloy and a method for preparing the nickel-iron-based alloy with the anti-oxidation coating on the surface, comprising the following steps:

[0046] Preparation of lanthanum zirconate target: prepare lanthanum nitrate and zirconium oxychloride starting materials at a molar ratio of 1:1, load them into a ball mill, add anhydrous ethanol and zirconium oxide balls into the ball mill in the mass ratio of the starting materials to anhydrous ethanol and zirconium oxide balls of 1:2:4, and ball mill them on a ball mill for 20 hours. Place the ball milled product in an oven at 80°C for 72 hours, and then sieve the sample with an 80-mesh screen. The sieved powder is compacted into a mold to form an embryo, and the embryo is placed on a ceramic pad and placed in a box furnace as a whole. The temperature is slowly increased from room temperature to 1020°C at a heating rate of 4°C / min, kept warm for 3 hours, and then cooled to room temperature at a rate of 10°C / min to obtain a pretreated embryo. The pretreated embryo is loaded into a ball mill and ball milled on a ball mill for 20 hours. The obtained powder is pressed into a mold, and then an isostatic pressing device is used to maintain pressure at 300MPa for 5 minutes to obtain a dense embryo. The dense embryo obtained after isostatic pressing is placed on a ceramic pad and put into a box furnace as a whole. The temperature is slowly increased from room temperature to 1400°C at a heating rate of 4°C / min, kept at this temperature for 2.5 hours, and then cooled to room temperature at a rate of 10°C / min to obtain the lanthanum zirconate target after final treatment.

[0047] Preparation of anti-oxidation coating: The lanthanum zirconate target was fixed on the target holder of the working chamber, and the nickel-iron based sample was fixed on the sample holder. The working chamber was evacuated by mechanical pump and molecular pump successively, so that the vacuum degree of the working chamber was no higher than 1×10 -4Pa. The sample holder and the nickel-iron based sample fixed on it were heated to 650°C, then the molecular pump was turned off, and a mixed protective atmosphere of high-purity argon (content: 99.999%) and high-purity oxygen (content: 99.99%) with a volume ratio of 4:1 was introduced into the working chamber, and a mechanical pump was used to adjust the working chamber air inlet and outlet to reach a balance, and the equilibrium pressure was 12 Pa. The laser energy was adjusted to 270 J, the pulse frequency was 4 Hz, the distance between the target and the sample was 5 cm, and the pulse laser deposition time was 3 h to obtain a nickel-iron based alloy with an anti-oxidation coating on the surface.

[0048] Figure 2 This is the working window for preparing lanthanum zirconate coating on nickel-iron based high temperature alloy by pulsed laser deposition method in Example 1 of the present invention. It can be seen that the plume morphology produced by the interaction between the pulsed laser and the target material is droplet-shaped. During the expansion of the plume, the central ablation high-density particle flow is at a certain distance from the alloy surface.

[0049] Figure 3 This is the X-ray diffraction pattern of the nickel-iron based alloy with an anti-oxidation coating on the surface prepared in Example 1 of the present invention. The results show that in addition to the characteristic diffraction peaks of the nickel-iron based high-temperature alloy substrate, the characteristic diffraction peaks of the lanthanum zirconate coating can also be observed, indicating that the lanthanum zirconate phase is prepared on the nickel-iron based high-temperature alloy substrate.

[0050] Figure 4 This is a SEM image of the nickel-iron based alloy with an anti-oxidation coating on the surface prepared in Example 1 of the present invention. From the SEM morphology, it can be seen that the coating is dense.

[0051] Figure 5 This is the EDS spectrum of the nickel-iron based alloy with an anti-oxidation coating on the surface prepared in Example 1 of the present invention. The corresponding element contents are shown in Table 1 below.

[0052] Table 1 Element content of alloy

[0053] element C O Al Ti Cr Fe NI Co Zr La W Wt% 5.44 7.87 1.12 0.92 15.88 22.34 37.7 0.09 3.12 4.71 0.81 At% 8.15 13.75 0.81 0.37 10.29 12.44 39.83 0.62 6.61 6.60 0.53

[0054] It can be seen from the figure that in addition to the alloy matrix elements, the absorption peaks of La and Zr elements can also be observed, further indicating that La2Zr2O7 coating can be prepared on the nickel-iron based high temperature alloy, in which the atomic percentages of La and Zr elements are 6.60% and 6.61%, respectively, which is close to the ideal ratio of metal atoms in the coating of 1:1.

[0055] The tensile properties of the nickel-iron based samples before the preparation of the anti-oxidation coating (alloy without anti-oxidation coating on the surface) and the nickel-iron based alloy with anti-oxidation coating on the surface after the preparation (alloy with anti-oxidation coating on the surface) were tested at 650°C. The strength and plasticity data are shown in the table below. It can be seen from the results that the mechanical properties of the alloy itself are not much different before and after the preparation of the anti-oxidation coating (RSD<3%). Therefore, the technical method described in this embodiment can achieve the purpose of alloy protection without affecting the mechanical properties of the alloy.

[0056] Table 2 Properties of the alloy before and after the deposition of the anti-oxidation coating

[0057]

[0058]

[0059] Example 2

[0060] The present embodiment provides an anti-oxidation coating for the surface of a nickel-iron-based alloy and a method for preparing the nickel-iron-based alloy with the anti-oxidation coating on the surface, comprising the following steps:

[0061] Lanthanum nitrate and zirconium oxychloride starting materials were prepared in a molar ratio of 1:1 and loaded into a ball mill. Anhydrous ethanol and zirconium oxide balls were added to the ball mill in a mass ratio of 1:4:7 to the starting materials, anhydrous ethanol and zirconium oxide balls, and ball milled on a ball mill for 24 hours. The ball milled product was placed in a 100°C oven for drying for 50 hours, and then the sample was sieved using an 80-mesh screen. The sieved powder was compacted into a mold to form an embryo, and the embryo was placed on a ceramic pad and placed in a box furnace as a whole. The temperature was slowly increased from room temperature to 1100°C at a heating rate of 5°C / min, and the temperature was kept for 2.5 hours, and then the temperature was cooled to room temperature at a rate of 14°C / min to obtain a pretreated embryo. The pretreated embryo was loaded into a ball mill and ball milled on a ball mill for 24 hours. The obtained powder was pressed into a mold, and then an isostatic pressing device was used to maintain a pressure of 250MPa for 7 minutes to obtain a dense embryo. The dense embryo obtained after isostatic pressing is placed on a ceramic pad and put into a box furnace as a whole. The temperature is slowly increased from room temperature to 1480°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, and then cooled to room temperature at a rate of 14°C / min to obtain the lanthanum zirconate target after final treatment.

[0062] The lanthanum zirconate target was fixed on the target holder of the working chamber, and the nickel-iron based sample was fixed on the sample holder. The working chamber was evacuated by mechanical pump and molecular pump successively, so that the vacuum degree of the working chamber was no higher than 1×10 -4Pa. The sample holder and the nickel-iron based sample fixed on it were heated to 570°C, then the molecular pump was turned off, and a mixed protective atmosphere of high-purity argon (content: 99.999%) and high-purity oxygen (content: 99.99%) with a volume ratio of 5:1 was introduced into the working chamber, and a mechanical pump was used to adjust the working chamber air inlet and outlet to reach equilibrium, and the equilibrium pressure was 15 Pa. The laser energy was adjusted to 220 J, the pulse frequency was 2 Hz, the distance between the target and the sample was 4 cm, and the pulse laser deposition time was 3.5 h, and a nickel-iron based alloy with an anti-oxidation coating on the surface was obtained.

[0063] Figure 6 This is the working window for preparing lanthanum zirconate coating on nickel-iron based high temperature alloy by pulsed laser deposition method in Example 2 of the present invention. It can be seen that the plume morphology produced by the interaction between the pulsed laser and the target material is droplet-shaped. During the expansion of the plume, the central ablation high-density particle flow is at a certain distance from the alloy surface.

[0064] Figure 7 This is a SEM picture of the nickel-iron based alloy with an anti-oxidation coating on the surface in Example 2 of the present invention. It can be seen from the SEM that the coating is dense.

[0065] Figure 8 This is the EDS spectrum of the nickel-iron based alloy with an anti-oxidation coating on the surface of Example 2 of the present invention, and the corresponding element contents are shown in Table 3 below.

[0066] Table 3 Element content of alloy

[0067] element C O Al Ti Cr Fe NI Co Zr La W Wt% 5.31 6.54 1.19 0.91 13.16 20.82 43.86 0.08 2.84 4.33 0.96 At% 8.34 10.97 0.95 0.35 8.81 10.74 46.60 0.56 6.02 5.99 0.67

[0068] It can be seen from the figure that in addition to the alloy matrix elements, the absorption peaks of La and Zr elements can also be observed, further indicating that La2Zr2O7 coating can be prepared on the nickel-iron based high temperature alloy, in which the atomic percentages of La and Zr elements are 5.99% and 6.02%, respectively, which is close to the ideal ratio of metal atoms in the coating of 1:1.

[0069] Example 3

[0070] This embodiment provides an anti-oxidation coating for the surface of a nickel-iron-based alloy and a method for preparing a nickel-iron-based alloy with an anti-oxidation coating on the surface, which is basically the same as Example 2, except that during the pulse laser process, the laser energy is adjusted to 400J.

[0071] from Fig. 9The SEM morphology shows that there are many large particles on the coating surface. This is because the target surface absorbs more energy under high laser energy, the target surface peeling is deepened, and the plasma can obtain high energy and high flight speed. Its high-energy particles collide violently with the substrate, and the generated reverse particle flow is prone to form vacancy defects. On the other hand, the micro-explosion on the target surface is enhanced. While the high-energy plasma flies to the substrate, the proportion of large particles increases, and the larger ion clusters are not diffused in time, causing the large liquid particles on the film surface to condense, affecting the final film quality.

[0072] Comparative Example 1

[0073] This comparative example provides an anti-oxidation coating for the surface of a nickel-iron-based alloy and a method for preparing a nickel-iron-based alloy with an anti-oxidation coating on the surface, which is basically the same as Example 2, except that during the pulsed laser process, the laser energy is adjusted to 100J.

[0074] from Fig.10 The SEM morphology shows that the coating surface crystallization effect is poor, and the typical lanthanum zirconate crystal morphology cannot be observed. This is because the laser energy is low, the energy obtained by the plasma is low, the expansion distance is short, and the desorption rate of the adsorbed particles on the substrate is high, which seriously affects the crystallization and growth of the coating on the alloy bottom.

[0075] Comparative Example 2

[0076] This comparative example provides an anti-oxidation coating for the surface of a nickel-iron-based alloy and a method for preparing a nickel-iron-based alloy with an anti-oxidation coating on the surface, which is basically the same as Example 1, except that the deposition temperature is 900°C, and only high-purity oxygen (content: 99.99%) is introduced into the working chamber without argon.

[0077] Fig.11 It is the X-ray diffraction pattern of the nickel-iron based alloy with an anti-oxidation coating on the surface in Comparative Example 2 of the present invention. The results show that, in addition to the characteristic diffraction peaks of the nickel-iron based high temperature alloy substrate, characteristic diffraction peaks of the oxidation phase and weaker characteristic diffraction peaks of the lanthanum zirconate coating can also be observed, indicating that when the temperature is high and the working atmosphere is entirely composed of high-purity oxygen components, it is easy to cause oxidation of the metal substrate itself, which is not conducive to the crystallization of the lanthanum zirconate coating on the substrate.

[0078] Experimental Example 1 Investigation of Final Treatment Temperature

[0079] A dense embryo was prepared according to the method of Example 1, and the dense embryo obtained after isostatic pressing was slowly heated from room temperature to different final treatment temperatures at a heating rate of 4°C / min, kept warm for 2.5 hours, and then cooled to room temperature at a rate of 10°C / min to obtain a lanthanum zirconate target after final treatment. The relative density of the target obtained at different target final treatment temperatures was tested.

[0080] Figure 1 A relationship diagram of the relative density of the target material obtained by using different target material final treatment temperatures is shown. It can be seen from the figure that when the target material final treatment temperature is 1300°C to 1500°C, the target material density reaches about 99%, indicating that by adopting the preferred conditions of the invention, a target material with higher density can be obtained within a shorter heat treatment time.

[0081] Experimental Example 2 Antioxidant Performance

[0082] The nickel-iron-based alloys with anti-oxidation coatings on the surfaces obtained in each group of examples and comparative examples were placed in a saturated steam environment at 650°C for 1000 h, and the oxidation weight gain (mg / cm 2 ), the results are shown in the following table and Fig.12 shown.

[0083] Table 4 Oxidation resistance of nickel-iron based superalloy

[0084] <![CDATA[Oxidation weight gain under saturated steam (mg / cm 2 )]]> Example 1 0.06 Example 2 0.08 Example 3 24.8 Comparative Example 1 35.0 Comparative Example 2 48.3

[0085] The results show that compared with Comparative Examples 1 and 2, the lanthanum zirconate coatings obtained in Examples 1-3 of the present invention have significantly improved oxidation resistance in a saturated steam environment. In particular, in Examples 1 and 2, the oxidation weight gain of the nickel-iron-based high-temperature alloy under saturated steam is less than 0.01 mg / cm 2 , the antioxidant performance is further improved.

[0086] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface, characterized in that: The steps include: Preparation of lanthanum zirconate target, the preparation method of the lanthanum zirconate target comprises the following steps: using lanthanum salt and zirconium salt as starting materials, dispersing the starting materials in anhydrous ethanol and performing a ball milling in the presence of a grinding medium; drying and compacting the ball milled product into an embryo, and sintering the embryo once; performing a second ball milling and pressing of the embryo after the first sintering; performing a second sintering of the pressed embryo to obtain a lanthanum zirconate target; the first sintering is: heating to 1000-1100°C at a heating rate of 3-5°C / min and keeping the temperature at this temperature for 2-3h, and then cooling at a cooling rate of 10-15°C / min; the second sintering is heating to 1300-1500°C at a heating rate of 3-5°C / min and keeping the temperature at this temperature for 2-3h, and then cooling at a cooling rate of 10-15°C / min; Using nickel-iron-based alloy as substrate, pulsed laser deposition method is used to deposit lanthanum zirconate anti-oxidation coating on the substrate surface; During the pulse laser deposition process, the substrate temperature is 550-800°C, the laser energy is 200-400J, the pulse frequency is 2-6Hz, the distance between the lanthanum zirconate target and the substrate is 4-5cm, a mixed atmosphere of oxygen and inert gas with a volume ratio of 4-6:1 is used as the protective atmosphere, and the equilibrium gas pressure is 10-15Pa.

2. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 1, characterized in that: The deposition time of pulsed laser deposition is 3-4h.

3. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 1 or 2, characterized in that: The laser energy of pulsed laser deposition is 200-300J.

4. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 1, characterized in that: The lanthanum salt is lanthanum nitrate, and the zirconium salt is zirconium oxychloride.

5. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 4, characterized in that: The molar ratio of lanthanum nitrate to zirconium oxychloride is 1:

1.

6. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 1, characterized in that: The mass ratio of the starting material to anhydrous ethanol and grinding medium is 1:2-4:4-8.

7. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 6, characterized in that: The grinding media is zirconia balls.

8. The method for preparing an anti-oxidation coating on a nickel-iron-based alloy surface according to claim 1, characterized in that: The primary ball milling and / or secondary ball milling is performed on a planetary ball mill for 16-24 hours; and / or the drying method is oven drying at a temperature of 80°C-100°C for 48h-72h; and / or the pressing pressure is 200-300MPa for 5-10min.

9. An anti-oxidation coating for the surface of a nickel-iron-based alloy obtained by the preparation method described in any one of claims 1 to 8.

10. The anti-oxidation coating for the surface of nickel-iron based alloy according to claim 9, characterized in that: The chemical composition of the anti-oxidation coating is lanthanum zirconate La2Zr2O7.

11. A method for preparing a nickel-iron based alloy having an anti-oxidation coating on the surface, characterized in that: The invention comprises a method for preparing an anti-oxidation coating for the surface of a nickel-iron-based alloy as described in any one of claims 1 to 8.

12. A nickel-iron based alloy having an anti-oxidation coating on its surface obtained by the preparation method according to claim 11.

Citation Information

Patent Citations

  • Method for preparing lanthanum zirconate powder

    CN101407336A

  • Nanocomposites for ultra high density information storage, devices including the same, and methods of making the same

    US20120033331A1